Desain Solusi Pembelajaran PAI Berbasis Flipbook Digital dan OBE di SMA 15 Adidarma Banda Aceh - Radhiah Radhiah; Sukma Juita; Faiza Nudia; Hamdi Yusliani (Indo Publishing, 2026)
This study developed a learning solution for Islamic Religious Education by integrating digital flipbooks and Outcome Based Education at SMA 15 Adidarma Banda Aceh. The study emerged from the need for learning that is more engaging, measurable, and compatible with students’ digital learning habits. A descriptive qualitative approach was used through classroom observation, interviews with PAI teachers, and analysis of instructional documents. The findings indicate that learning becomes more focused when teachers align learning outcomes, interactive flipbook materials, project-based activities, and authentic assessment. Digital flipbooks make PAI content easier to access and review, while OBE keeps learning oriented toward clear final outcomes The study shows that this design is feasible as a model for strengthening PAI learning in secondary schools.